Britain and the Netherlands - Bromley, J. S. author. aut Link
VIII, 212 p. 1 illus.
Keywords: AS Dr. Coen Tamse points out in the introductory essay specially written for this volume, what we call myths are all too often the errors and misconceptions of others. Time being short and human un derstanding imperfect, it is wise to suppose that posterity will convict us all of thinking and acting in some sort within mythological uni verses; only a dead myth is by common consent recognized as a false reading of reality. And yet, in our troubled century, we have witnessed the deliberate fabrication of mythologies, apart from the inheritance of earlier growths like those which still feed nationalism and anti Semitism. It almost looks as if mass democracies positively require neatly packaged and emotionally charged explanations of the social and political environment as a substitute for religion. At all events, the modern science of public relations has advanced far enough for cer tain regimes, or for those who seek to overthrow them, to make a calculated appeal to the vanities, anxieties and frustrations of ordinary people by offering highly simplified explanations of a baffling world, often in easily grasped pictorial or dramatic forms, whether the object is to condition obedience or incite to 'struggle'. The advent of the mass media is generally, if unfairly, taken to have opened limitless new op portunities for the manipulation of our thought-processes, even below the threshold of consciousness.